Decay rate measurements $^{137}$Cs at Jánossy Underground Research Laboratory - Fenyvesi, Edit; Barnaföldi, Gergely Gábor; Kiss, Gábor Gyula; Molnár, Dénes (2024)
The question whether an annual modulation is observable during nuclear decay rate measurements has long been the subject of research. One of the possible explanations for the annual variations would be the effect of solar neutrinos, the flux of which changes in correlation with the Earth-Sun distance. A decay rate measurement with a $^{137}$Cs source and a HPGe detector is currently being conducted 30 meters below the ground at Jánossy Underground Research Laboratory (Csillebérc, Hungary). The laboratory is part of the Vesztergombi High Energy Laboratory (VLAB), one of the TOP 50 research infrastructures in Hungary. From October 2022 to March 2023, data of six months' worth has been collected, and hence this is a new opportunity to check whether the annual variation in decay rate can be observed. The laboratory, the experiment, the data processing method, and the first results are presented in this study.